Single Parent Women's Strategy in Providing Children's Education Needs: A Case Study - Aryani, Endah Iri; Lindawati, Yustika Irfani (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Single-parent women often face complex challenges in meeting the educational needs of their children due to financial, social, and emotional constraints. Understanding how they navigate these challenges is essential for developing supportive policies and interventions. Objective: This study aims to explore the strategies employed by single-parent women in fulfilling their children's educational needs. Method: A descriptive qualitative approach was used, with the research conducted in Pasanggrahan Village, Tangerang Regency. Data were collected through observations and in-depth interviews with selected informants. To ensure data validity, triangulation techniques and informant reviews were employed. Data analysis was carried out in four stages: data collection, data reduction, data presentation, and conclusion drawing. Result: The study found that the strategies adopted by single-parent women vary based on their individual backgrounds and specific circumstances. Most respondents manage their limited financial resources by prioritizing essential household expenses, especially those related to education, and by differentiating between primary, secondary, and tertiary needs. Conclusion: Single-parent women in Pasanggrahan Village demonstrate adaptive and resourceful financial management strategies to ensure their children's educational continuity, despite facing socioeconomic limitations. Contribution: This research provides insights into the economic coping mechanisms of single mothers, offering a foundation for community support programs and policy initiatives aimed at enhancing access to education for children from single-parent households.